Pandemi Covid 19, Kinerja Keuangan Dan Cumulative Abnormal Return (CAR) - Pipin Kurnia; Restu Agustia; Edfan Darlis; Supriono Supriono; Sem Paulus Silalahi (Universitas Muhammadiyah Malang, 2022)
The purpose of this study is to empirically prove the effect of positive confirmed cases of covid 19, confirmed death cases of covid 19, company's financial performance on cumulative abnormal return (CAR). The sample used is restaurant, hospitality and transportation companies listed on the Indonesia Stock Exchange for the period 2019-2020. This research uses multiple regression method. The sample in this company amounted to 81 companies and the sampling method was purposive sampling method. The results of this study prove that positive confirmed cases of covid 19, positive confirmed death cases of Covid 19, liquidity, leverage and company size (Size) have no affect on CAR during the Covid 19 pandemic. While ROA (Return on Assets) affects CAR during the COVID-19 pandemic. This research adds to the literature on the impact of the coronavirus pandemic (covid 19) and how the company's performance on the company's stock price during the coronavirus pandemic and until now, this pandemic has not ended. Assist the government in making decisions in making policies, especially when the implementation of restrictions on community activities (PPKM) takes place, whether it will impact losses for companies in Indonesia.